Delivery of mRNA Vaccine against SARS-CoV-2 Using a Polyglucin:Spermidine Conjugate - Karpenko, Larisa I. (Vaccines (Basel), 2021)
One of the key stages in the development of mRNA vaccines is their delivery. Along with liposome, other materials are being developed for mRNA delivery that can ensure both the safety and effectiveness of the vaccine, and also facilitate its storage and transportation. In this study, we investigated the polyglucin:spermidine conjugate as a carrier of an mRNA-RBD vaccine encoding the receptor binding domain (RBD) of the SARS-CoV-2 spike protein. The conditions for the self-assembling of mRNA-PGS complexes were optimized, including the selection of the mRNA:PGS charge ratios. Using dynamic and electrophoretic light scattering it was shown that the most monodisperse suspension of nanoparticles was formed at the mRNA:PGS charge ratio equal to 1:5. The average hydrodynamic particles diameter was determined, and it was confirmed by electron microscopy. The evaluation of the zeta potential of the investigated complexes showed that the particles surface charge was close to the zero point. This may indicate that the positively charged PGS conjugate has completely packed the negatively charged mRNA molecules. It has been shown that the packaging of mRNA-RBD into the PGS envelope leads to increased production of specific antibodies with virus-neutralizing activity in immunized BALB/c mice. Our results showed that the proposed polycationic polyglucin:spermidine conjugate can be considered a promising and safe means to the delivery of mRNA vaccines, in particular mRNA vaccines against SARS-CoV-2.